Placenta: motivations, uses, and meanings in south central Chile - Rodrigo Contreras Molina; Marcelo Berho Castillo (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2022)
Motivations, uses, and meanings given to the placenta by women and men in south central Chile are analyzed, following the implementation of Technical Standard 189 by the Ministry of Health, which allowed people to request their placentas after giving birth on hospital grounds. From an ethnographic approach to the sociocultural uses of placentas, in-depth interviews were carried out with women and their partners between July and November 2019; individual narratives were recorded, as well as conversations between Mapuche women and men who had requested their placenta in three Chilean regions (Araucania, Metropolitan, and Arica and Parinacota). This article focuses on four cases that illustrate the diversity of practices and knowledge surrounding the placenta - inscribed in sociocultural, territorial, political, spiritual, and religious frameworks - according to actors' sociocultural origins. To conclude, the cases are compared in order to highlight both similarities and differences, and some challenges derived from the findings are considered.